Human Papillomavirus Vaccine – Where are We Now? - Paczos, MD, Tamera A.; Liu, MD, PhD, Weiguo; Chen, MD, PhD, Frank (North American Journal of Medicine and Science, 2010)
This paper attempts to review the currently available relevant information about the two widely distributed human papillomavirus (HPV) vaccines in use today and place it in an easily understandable and readable format for busy clinicians to access. The article briefly reviews the background of the HPV virus and cervical cancer. It details to the vaccines currently licensed for use in the United States, Gardasil and Cervarix, going over the mechanisms of action for both, as well as administration routes. Efficacy of the vaccines was discussed in terms of the available phase II and phase III trial data available to date. Vaccination in males, cost-effectiveness and social acceptance were also reviewed. A brief discussion about the future development of second generation HPV vaccines was included. Although the data collected to date are promising, there is still much to learn about exactly what the future impact of the HPV vaccine will be in the United States and globally. Further research and analysis are necessary to determine the long term medical, social, and economic impact of the HPV vaccine.